Direito à participação popular no licenciamento ambiental brasileiro: análise do projeto Santa Quitéria de mineração de urânio e fosfato - Santos, Julianne Melo dos (2016)
The environmental licensing of large-scale activity is legal instrument for safeguarding the fundamental rights to life, to health and the environment for present and future generations. However, to ensure its effectiveness is necessary that the analysis of social and environmental viability is performed in order to facilitate the participation of people affected by the projects. Thus, this work yearns investigate the right to public participation in the licensing process, based on the understanding that the asymmetry of power between the state, entrepreneur and hit permeates environmental conflicts, with the analysis parameter licensing project Santa Quiteria mining uranium and phosphate. Through documentary literature and case study and from the understanding of the current licenciatório procedure are glimpsed-limits, prospects and the challenges that pervade the realization of the democratic principle. The study is the foundation of supply (in) environmental justice to understand the environmental assessment process in the licensing of the bulge in this case and determine whether a more effective environmental and human rights protection can be guaranteed through popular participation.